Three‐dimensional CT observation of position and movability of the scapula in the horse using carcasses of Falabella. (29th January 2019) - Endo, Hideki; Nguyen, Son Truong; Yoshida, Masataka; Kudo, Kohei
Abstract: The three‐dimensionally real position and movement of the scapula in the lateral side of the ribcage could not be clarified in the horse, since the body size of the horse is too large to apply the CT scanning and image analysis methods. In this study, therefore, we examined the position and the movability of scapula using a carcass of the Falabella which is one of the smallest breeds of the horse. The whole skeletal system in thoracic part of the Falabella could be three‐dimensionally observed by CT scanning method. The three‐dimensional images show that the scapula cranially slides and the ventral part of the scapula dorso‐cranially rotates, when the shoulder joint moves to the most cranial position as simulation. The three‐dimensional rotation angle was approximately 10 degrees. As a result of comparative osteology of the scapula between Falabella and the large draft horse, the infraspinous fossa was caudally enlarged in the larger draft horse, whereas the Falabella had narrower infraspinous fossa. We suggest that it may be due to the adaptational morphological change in the scapula bearing various body weights among breeds. The three‐dimensional CT image analysis and the simulation in carcass contribute to the analysis of the bone movements of the horse during walking and running locomotion as well as the motion analysis from external functional‐morphological data.